Book review of D. Kapantais and G. Karamanolis (eds) "Aristotle Prior Analytics I1-22: The Aristotelian syllogistic" - Stephanou, Yannis (Neusis, 2025)
This is a book review of the volume "Aristotle Prior Analytics I1-22: The Aristotelian syllogistic", edited by D. Kapantais and G. Karamanolis.